Development of an Online Registration System for Loss Recommendation Letters at Temanggung Police Department - Galih Yunus Al Anas; Edy Supriyanto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
Advancements in information technology have markedly enhanced the efficiency of public services, notably at Temanggung Police Station. Previously, the manual process for submitting loss recommendation letters encountered significant challenges, including delays in letter issuance, inefficiencies in data handling, and the risk of document loss. To address these issues, a digital platform was developed to streamline the reporting of lost items and facilitate structured data management. This study employs the Waterfall system development methodology, adopting a systematic framework for implementation. Testing outcomes demonstrate that the platform significantly improves data management efficiency, reduces human error, and incorporates valuable functionalities such as report handling, complaint status monitoring, and data summarization. Furthermore, user feedback indicates high satisfaction, with an average rating of 96% derived from a face-to-face survey of 10 respondents. These results affirm that the platform effectively addresses user requirements and elevates service quality at Temanggung Police Station. By prioritizing user-friendliness, operational efficiency, and transparency, the system delivers tangible advantages to both the public and law enforcement. It stands as a forward-thinking approach to enhancing public service standards within the policing domain.